PENGGUNAAN EKSTRAKSI SEKUENSIAL UNTUK SPESIASI LOGAM BERAT DI SEDIMEN - Lestari Lestari (Pusat Penelitian Oseanografi LIPI, 2017)
THE USE OF SEQUENTIAL EXTRACTION PROCEDURES FOR HEAVY METAL SPECIATION IN SEDIMENT. Metals accumulation in sediments from both natural and anthropogenic sources occurs in the same way, making it difficult to identify and determine the origin of heavy metals present in the sediments. Moreover, the total concentration of metals often does not accurately represent their characteristics and toxicity. In order to overcome the mentioned obstacles, it is necessary to evaluate the environment effect. Single extraction is thus used generally to provide a rapid evaluation of the exchangeable metal fraction in sediments. However, complicated sequential extraction procedures are used to provide more detailed information regarding different metal phase associations.